CREATIVE ACCOUNTING AND SHAREHOLDERS WEALTH MAXIMIZATION IN NIGERIAN QUOTED BANKS - Dr. Solomon Egbe (American Journals Publishing, 2023)
This work seeks to study and reveal major threat creative accounting posed on shareholders as a result different accounting method used by banks or organization. The research work focuses on creative accounting and shareholders wealth maximization in Nigerian quoted banks. The main objective of this study is to examine the influence of creative accounting on shareholders wealth maximization in Nigerian quoted banks. Nine (9) hypothesis were formulated survey design was adopted with a sample size of one hundred and fifty (150). The questionnaires were instrument used for data collection. The data collected were subject to simple validity and reliability test: The analysis of data was based on statistical tools such as percentage, frequency and mean, while correlation analysis was used to test the hypothesis. Some of the findings reveal that creative accounting affects shareholders wealth at the long- run and their possible investment decision. Based the finding it was recommended that investors through the financial sector regulatory authorities should encourage banks to engage in creative accounting but at the same time closely regulate such development to assure of its integrity in other to enhance effective earnings per share and return on investment.
Keywords: Earnings after Tax. Share price. Shareholders. Creative accounting. Return on Investment.